Monte-Carlo Simulation of Technological Risks in Pig Farm - Szőke, Szilvia; Nagy, Lajos; Balogh, Péter (Acta Agraria Kaposváriensis, 2010)
The study was based on data from an Ltd.’s 1100-swine farm. Our aims were to study the operation and expected results of the farm’s operation in 2009. The significant independent variables, their ranges and probability distributions, and the correlation between them were inputs to the model. The values of the variables were produced using a random number generator. The computer simulation was performed using @Risk (Palisade Corporation) software. The study concentrates on the factors affecting the number of offspring (piglets). Model inputs were the mating, mortality and farrowing rates; the costs and the income values based on these rates have been analysed as the output data of the model. The results indicate that there is a modest correlation between the fattening pig price and per unit profit (Spearmann’s rank correlation coefficient: ρ = 0.585); the strongest correlation (-0.73 ≥ ρ ≥ -0.76) is between the fodder prices and per unit profit. The 10,000 model runs yielded the mean is 905 million HUF of the total cost, the mean value is 1005 million HUF of the total income of the swine farm. In case of the total profit: the mean is 101 million HUF. The probability of the loss in farm’s operation is 13.02 percent considering the above mentioned model settings.
Keywords: pig production; computer simulation